Strong, detachable, and self-healing dynamic crosslinked hot melt polyurethane adhesive. (15th July 2019) - Wang, Shuliang; Liu, Zenghe; Zhang, Luzhi; Guo, Yifan; Song, Jianchun; Lou, Jiaming; Guan, Qingbao; He, Chuanglong; You, Zhengwei
Abstract : A dynamic oxime–carbamate based polyurethane hot melt adhesive was developed with outstanding adhesion performance to multiple substrates, and detachable and self-healing properties. Abstract : As a group of environmentally friendly adhesives, polyurethane hot-melt adhesives (HMAs) are used widely. However, existing thermoplastic (TPU) and thermoset (PUR) polyurethane HMAs have certain shortcomings. The adhesion strength and solvent resistance of TPU-HMAs are relatively poor owing to their linear structure. PUR-HMAs are non-reworkable and unrecyclable with low initial adhesion strength. These features greatly limit their applications. Herein, we used reversible oxime–carbamate bonds to build a dynamically crosslinked polyurethane HMA (DPU-HMA), which combines the advantages of TPU-HMAs and PUR-HMAs. Lap shear tests of stainless steel showed that the DPU-HMA had initial (3.47 ± 0.93 MPa after 5 min curing) and ultimate (5.71 ± 0.72 MPa after 1 day curing) adhesion strengths that were much higher than those for the commercial adhesive 3M PUR-HMA (0.02 ± 0.01 MPa after 5 min curing; 4.07 ± 0.13 MPa after 14 days curing). The DPU-HMAs retained moderate lap shear strength in solvent (acetone), whereas TPU-HMAs were completely dissolved. The DPU-HMAs were effective in bonding multiple substrates including metal, plastic, wood, and composites. Furthermore, the DPU-HMAs possessed smart features, such as debonding on demand and self-healing owing to their dynamic network. We expect that this new type of adhesive will be useful for applications in electronics assembly, and the automotive, and aerospace fields. The molecular design strategy might also be applicable for other adhesive systems.